Academic Senate Minutes 2010-09-30 - Academic Senate:::::::::
Chair Report. Agenda amended and approved. President Report. Provost Report. Vice President of Administration and Finance Report. Adding Senate Budget Subcommittee to the by-laws approved. Chair-Elect Report. Special Report: Faculty Workstation Refresh Program. Final Report from the Ad-Hoc Diversity Committee. Statewide Senator Report. Revision to Learning Objectives for Areas A and C – First Reading.